The Impact of Bacterial Dysbiosis on the Development of Pancreatic Cancer and Its Treatment in Humans? - Mikołajczyk Agata; Wardak Amelia; Głuszek Stanisław; Adamus-Białek Wioletta (Postępy Mikrobiologii, 2025)
Pancreatic cancer is one of the deadliest types of cancer and is still difficult to treat, despite recent medical advances. Many studies show correlations between the human oral and intestinal microbiota and pancreatic cancer. The mechanism of action of microorganisms on the pancreatic microenvironment is still not fully understood. The aspect of immune response related to treatment and the microorganisms present has also been addressed. This review presents current evidence on the human microbiota, mainly focusing on its bacterial contribution and influence, and identifies the areas that may benefit most from earlier diagnosis and the potential for less invasive treatment of pancreatic cancer. A review of all the latest literature (n=86) in peer-reviewed English-language journals with an Impact Factor from PubMed (NCBI) and Google Scholar was conducted; most studies concerned the analysis of bacteria in the human microbiota or in a mouse model.